The Cultural Unconscious of the ‘Mayyazhi River banks’ - Prof. A . Nujum (IRAYAM, 2024)
This paper explores the cultural unconscious and historical influences portrayed in M. Mukundan’s novel "Mayyazhippuzhayude Theerangalil," reflecting on 50 years since its first publication. It delves into how the novel interweaves the colonial and post-colonial narratives of Mayyazhi, a former French colony, illustrating the synthesis of historical facts and cultural perceptions. The analysis highlights how the novel encapsulates the dualities of history and culture, portraying a complex interplay between the colonizers and the native populace. The narrative strategy used in the novel is rooted in Michael Bhaktin’s concepts of dialogism and heteroglossia, emphasizing the polyphonic nature of the narrative that accommodates multiple cultural voices and perspectives. This study illuminates the evolution of a hybrid culture where French and indigenous elements amalgamate, creating a new cultural identity that transcends traditional barriers of caste and class, ultimately contributing to a nuanced understanding of cultural dynamism and colonial impact. The novel’s portrayal of the cultural unconscious offers profound insights into the transformative power of colonial history interlaced with the resilience of cultural identity, making it a critical literary work in modern Indian literature that resonates with contemporary issues of cultural integration and identity politics.